2008
DOI: 10.1007/s11240-008-9391-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of two phenotypes of Centella asiatica in Southern Africa through the composition of four triterpenoids in callus, cell suspensions and leaves

Abstract: Two morphologically distinct phenotypes of Centella asiatica (Type-1 and Type-2) in South Africa were compared in relation to the levels of triterpenoid saponins with the aim of assessing their potential for biotechnological manipulation of triterpenoid synthesis. The metabolites investigated included madecassoside and asiaticoside and their sapogenins madecassic-and asiatic acid; produced in cultured undifferentiated cells (cell suspensions and calli) and leaves. Weight determination in plant cell suspensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 23 publications
4
47
0
Order By: Relevance
“…The observation of greater active ingredient content in morphotype A compared to morphotype B may support the findings by James et al [25], who estimated the triterpenoid content of leaves of morphotype B harvested in South Africa at between 1.8 and 5%. These findings corroborate those of Rouillard-Guellec et al [3], who estimate that leaves of Malagasy origin (morphotype A) could be three to seven times richer in triterpenoids than those of Indian origin.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The observation of greater active ingredient content in morphotype A compared to morphotype B may support the findings by James et al [25], who estimated the triterpenoid content of leaves of morphotype B harvested in South Africa at between 1.8 and 5%. These findings corroborate those of Rouillard-Guellec et al [3], who estimate that leaves of Malagasy origin (morphotype A) could be three to seven times richer in triterpenoids than those of Indian origin.…”
supporting
confidence: 88%
“…Morphotype B (round leaves) seems to be widely distributed across Southeast Asia and Africa and could be the type species [25]. Morphotype A (reniform leaves), contrary to that stated by Boiteau [7], seems more specific to Madagascar.…”
mentioning
confidence: 62%
“…However, in some cases, the production of secondary products did not show a positive correlation with the maximal growth rate of the culture (Jacinda et al, 2008). Various reports have indicated that maximum production of flavonoid's achieved during the active growing stage of the cells (Zhao et al, 2001;Antonigni et al, 2007;Fu et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…It showed that higher concentrations of BAP gave better callus proliferation rates. Furthermore, a study by Jacinda et al (2008) revealed that they maintained the C. asiatica callus in the MS medium supplemented with 0.22 mg L −1 2,4-D and 0.23 mg L −1 BAP and managed to produce triterpenoids. It was found that TDZ generally tended to promote the formation of compact-green nodular callus (Murthy et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation